2021
DOI: 10.1136/bmjsem-2020-001025
|View full text |Cite
|
Sign up to set email alerts
|

Mental health among elite athletes in Norway during a selected period of the COVID-19 pandemic

Abstract: ObjectiveTo investigate the prevalence of mental health problems and satisfaction with life among different groups of elite athletes during a selected period of the COVID-19 pandemic and examine how COVID-19 related consequences were associated with these variables.DesignCross-sectional data collection during a selected period of the COVID-19 pandemic in Norway.Participants378 elite athletes, mean age 26.86 (range 18–59), 159 females and 219 males, divided into Olympic-level and Paralympic-level athletes (n=19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
2
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(65 citation statements)
references
References 16 publications
1
54
2
2
Order By: Relevance
“…In contrast to our findings, Gouttebarge and colleagues found moderate and moderate-to-severe depression levels in 12.9 (male) to 21.6% (female) of professional football players during the first COVID-19 lockdown period [27]. Pensgaard et al found depressive symptoms in 22.3% of a Norwegian sample of elite athletes in summer 2020 but did not report the symptom severity [29]. In a South African sample of elite and semi-elite athletes, almost half of them reported feeling depressed during the lockdown in spring 2020 [28].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to our findings, Gouttebarge and colleagues found moderate and moderate-to-severe depression levels in 12.9 (male) to 21.6% (female) of professional football players during the first COVID-19 lockdown period [27]. Pensgaard et al found depressive symptoms in 22.3% of a Norwegian sample of elite athletes in summer 2020 but did not report the symptom severity [29]. In a South African sample of elite and semi-elite athletes, almost half of them reported feeling depressed during the lockdown in spring 2020 [28].…”
Section: Discussioncontrasting
confidence: 99%
“…Depending on their sport (i.e., team vs. individual sports, summer vs. winter sports) and the season in which the lockdown was imposed, the routines of athletes were affected differently. An increased mental health burden in elite football players and athletes of other disciplines has already been described during the lockdown period in spring 2020 [20,[27][28][29][30].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…up to 6% low-risk, moderate-risk or problem gambling) Above non-problem gambling markedly less common than in the general population. Associations (including with gender) not reported Håkansson et al ( 2020b ) Sweden, elite athletes, top leagues of football, ice hockey, handball ( N = 274), assessed during COVID-19 Top national leagues (highest female leagues, highest male handball league and highest two male football and ice hockey leagues) PGSI (Wynne & Ferris, 2001 ), past 12 months Moderate-risk/problem gambling in 10% of men, and 0% of women Clear association of gambling problems with male gender Pensgaard et al ( 2021 ) Norway, several types of sports, assessed during COVID-19 (June–September, 2020), ( N = 378) Olympic/Paralympic athletes and other elite/semielite athletes Canadian Problem Gambling Index (CPGI, Wynne & Ferris, 2001 ) “Gambling problems” in 8.7% of men and 1.3% of women Gambling problems (definition unclear) markedly higher in males than in females, and lower in athletes reporting positive consequences of the COVID-19 situation …”
Section: Methodsmentioning
confidence: 99%
“…Mittel- und langfristig kann dies zu Motivationsverlust, Sinnfragen bezüglich der (professionellen) Sportausübung und weiterführend u.a. zu Schlafstörungen, depressiver Symptomatik und Essstörungen führen [25] . Eine enge sportmedizinische Begleitung, Thematisierung der Problematik und Austausch im medizinischen Team inklusive psychologischer/psychiatrischer Kollegen sowie die Kommunikation mit dem betreuenden Trainerteam (unter Wahrung der ärztlichen Schweigepflicht) ist erforderlich, um frühzeitig negative Tendenzen zu erkennen und entsprechend gegensteuern zu können [26] .…”
Section: Psychische Belastung Von Athleten Und Betreuernunclassified